Beban Kerja dan Faktor Kelelahan : Sebuah Path Analysis Produktivitas Operator di Kilang Paraxylene PT Kilang Pertamina Internasional RU IV Cilacap - Ach Suhairi; Heru Prasadja; Lamtiur H. Tampubolon (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to examine the influence of workload and fatigue on operator productivity at the Paraxylene Refinery of PT Kilang Pertamina Internasional RU IV Cilacap. Using a quantitative research method and a causal associative approach, data were collected via questionnaires from 64 employees selected through simple random sampling. The data were analyzed using multiple regression and path analysis techniques. The results indicate that workload has a significant positive direct effect on productivity, but a negative indirect effect through fatigue. Fatigue was found to have a significant negative impact on productivity and acts as a mediating variable in the relationship between workload and productivity. Simultaneously, workload and fatigue contribute 61.2% to variations in productivity. This study contributes to the literature by confirming fatigue as a significant mediator affecting operator performance in high-risk industrial settings.